Aplikasi Sistem Pakar Klasifikasi Kesehatan Lingkungan Permukiman Dengan Metode Certainty Factors - Joko Siswanto; Anas Azhimi Qalban; Sri Nilawaty Lahay; Joko Siswanto (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Settlements environmental health requirements that continue to grow and develop include 7 aspects. Stakeholders have difficulty classifying the environmental health of settlements, it takes a long time, is not accurate, and is incomplete. The settlements environmental health expert system application is built on a website using the Certainty Factor Method. Expert system application development adopts the Expert System Development Life Cycle (ESDLC) method. Applications are designed starting from reasoning and scoring, database design, context diagrams, and system flow charts. Expert system applications based on design were developed using the Notepad++ editor to write Hypertext Preprocessor (PHP) programs with the CodeIgniter framework. XAMPP is used to run databases using MySQL and Apache for local servers. The results of the comparison between manual calculations and applications have the same score. This can be used as evidence that the expert system application built can be used to help classify settlements environmental health. The results of the classification can be used as a reference for policies and forms of environmental health reporting in settlements every year by stakeholders.